Irritable bowel syndrome in celiac disease - relationships to celiac disease antibodies and levels of pro-inflammatory cytokines - Olano, Carolina (2020)
Background: Evidence indicates that low-grade inflammation can alter gastrointestinal motor and sensory function and might contribute to the genesis of symptoms in IBS. Objective: To examine relationships between IBS, disease antibodies and cytokine titers in celiac patients and a control group. Materials and methods: IBS, CD activity and serum levels of IL-6, IL-8 and IL12/23p40 were determined in celiac patients and controls. Results: 123 celiac patients were included, 89% were female. 59% demonstrated disease activity and 32% met IBS criteria. Prevalence of IBS was not different between patients who adhered or did not adhere to GFD as well as between patients with or without positive antibodies. Celiac patients had increased levels of IL-6, IL-8 and IL12/23p40 as compared to controls. Higher levels of cytokines were found in celiac patients with IBS than in those without IBS. No difference in levels of cytokines was found between patients with and without CD positive antibodies. A significant negative correlation between the mental component of QoL and IL-6 and IL12/23p40 levels was found, but not with IL-8. Conclusion: Higher levels of inflammatory cytokines were found in CD patients with IBS than in either those without IBS or controls, indicating that IBS symptoms are associated with an increase in the inflammatory response s. These differences in cytokine levels were not related to CD antibodies status gesting that IBS, in CD, is related to a different inflammatory process than that which is relevant to CD.